Analytical and Experimental Approaches to Shot Peening - Prawoto, Yunan; Mazein, P G; Kosterin, A V (Bandung State Polytechnic (Politeknik Negeri Bandung), 2020)
This paper is a first attempt on analytical approach to shot peening. Shot peening improves the surface engineering quality by eliminating the tool marks, such as machining, grinding, stamping and other surface defects. Most importantly, the improvements of shot peening are produced by combination of compressive stress and cold work. Compressive stresses are beneficial in increasing resistances to fatigue failures, while the cold work effects of shot peening treatments can increase the surface hardness. Although shot peening is extensively used in the industry, its academic understanding is very low. Shot peening has been considered as a black art and black engineering in the industry. The focus of this research is to layout foundation of the shot peening research in academic world. Only then, will the research propel more systematically rather than via the conventional industrial trial and error approach. In this research, analytical approach with experimental verification is presented.